The p85 Regulatory Subunit of PI3K Mediates cAMP-PKA and Insulin Biological Effects on MCF-7 Cell Growth and Motility - E. Di Zazzo; A. Feola; C. Zuchegna; A. Romano; C. F. Donini; S. Bartollino; C. Costagliola; R. Frunzio; P. Laccetti; M. Di Domenico; A. Porcellini (The Scientific World Journal)
Recent studies have shown that hyperinsulinemia may increase the cancer risk. Moreover, many tumors demonstrate an increased activation of IR signaling pathways. Phosphatidylinositol 3-kinase (PI3K) is necessary for insulin action. In epithelial cells, which do not express GLUT4 and gluconeogenic enzymes, insulin-mediated PI3K activation regulates cell survival, growth, and motility. Although the involvement of the regulatory subunit of PI3K (p85αPI3K) in insulin signal transduction has been extensively studied, the function of its N-terminus remains elusive. It has been identified as a serine (S83) in the p85αPI3K that is phosphorylated by protein kinase A (PKA). To determine the molecular mechanism linking PKA to insulin-mediated PI3K activation, we used p85αPI3K mutated forms to prevent phosphorylation (p85A) or to mimic the phosphorylated residue (p85D). We demonstrated that phosphorylation of p85αPI3KS83 modulates the formation of the p85αPI3K/IRS-1 complex and its subcellular localization influencing the kinetics of the insulin signaling both on MAPK-ERK and AKT pathways. Furthermore, the p85αPI3KS83 phosphorylation plays a central role in the control of insulin-mediated cell proliferation, cell migration, and adhesion. This study highlights the p85αPI3KS83 role as a key regulator of cell proliferation and motility induced by insulin in MCF-7 cells breast cancer model.